On a Production Allocation and Distribution Problem - Mairs, Thomas G.; Wakefield, Glenn W.; Johnson, Ellis L.; Spielberg, Kurt (Management Science, 1978)
We describe a production allocation problem which was worked on at Frito-Lay and an integer programming model formulated for its solution. In connection with model formulation, we discuss estimation and collection of the required cost coefficients. Finally, we report on the use of two different linear programs, representing the same integer problem, which gave dramatically different running times to solve the integer programs. Some reasons for the improved running times are given.